1993
DOI: 10.1079/bjn19930150
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function in rats with iodine deficiency is not further impaired by concurrent, marginal zinc deficiency

Abstract: The hypothesis tested was that Zn deficiency aggravates impaired thyroid function as induced by I deficiency. In two separate experiments male rats were fed on diets either deficient in Zn or in I, or deficient in both. An identical, restricted amount of food was given to each rat so that body-weight gain of the experimental groups was comparable. Zn deficiency was evidenced by reduced tibia1 Zn concentrations. I deficiency was evidenced by goitre, reduced urinary I excretion, reduced plasma thyroxine concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…Serum Zn con centrations in the present study are in agree ment with the observations of other workers [9,11,12] who have also reported reduction in serum Zn concentrations in ZnD guineapigs. Growth retardation due to Zn deficiency in guinea-pigs as observed in the present study has also been reported in other species of animals [14], This might be due to impair ment of DNA synthesis since during Zn defi ciency the enzymes (thymidine kinase and DNA polymerase) and a hormone, somato medin C, required for DNA synthesis have been reported to be decreased [14,15], Sec ondly, hypothyroidism might have also con tributed to growth retardation [14], Lower values of serum T3 and T4 observed in ZnD guinea-pigs of the present study have also been found to be associated with Zn defi ciency in rats [2,3,5,16,17] and human beings [ 18]. Alteration in thyroid hormones as suggested by Morley et al [ 1 ] and Fujimoto et al [3] might partly be secondary to deficiency of vitamin A [19] which has been reported to be required for extrathyroidal conversion of T4 to T;, in the liver.…”
Section: Zinc Deficiency and Thyroidmentioning
confidence: 58%
See 2 more Smart Citations
“…Serum Zn con centrations in the present study are in agree ment with the observations of other workers [9,11,12] who have also reported reduction in serum Zn concentrations in ZnD guineapigs. Growth retardation due to Zn deficiency in guinea-pigs as observed in the present study has also been reported in other species of animals [14], This might be due to impair ment of DNA synthesis since during Zn defi ciency the enzymes (thymidine kinase and DNA polymerase) and a hormone, somato medin C, required for DNA synthesis have been reported to be decreased [14,15], Sec ondly, hypothyroidism might have also con tributed to growth retardation [14], Lower values of serum T3 and T4 observed in ZnD guinea-pigs of the present study have also been found to be associated with Zn defi ciency in rats [2,3,5,16,17] and human beings [ 18]. Alteration in thyroid hormones as suggested by Morley et al [ 1 ] and Fujimoto et al [3] might partly be secondary to deficiency of vitamin A [19] which has been reported to be required for extrathyroidal conversion of T4 to T;, in the liver.…”
Section: Zinc Deficiency and Thyroidmentioning
confidence: 58%
“…Alteration in thyroid hormones as suggested by Morley et al [ 1 ] and Fujimoto et al [3] might partly be secondary to deficiency of vitamin A [19] which has been reported to be required for extrathyroidal conversion of T4 to T;, in the liver. Indeed the interaction between Se and I with respect to T4 and T3 conversion has been reported [20] but a recent study [5] on Zn and I interaction revealed that Zn deficiency did not influence thyroid hor mone metabolism in iodine-deficient rats. In terestingly, the present study indicates that Zn deficiency may directly affect thyroid hor mone synthesis as evidenced by atrophy and degenerative changes in thyroid follicles of ZnD animals.…”
Section: Zinc Deficiency and Thyroidmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc deficiency depresses weight gain and causes numerous physiological abnormalities (19,26), including alterations in hormone metabo-lism (14,27). Several studies have been carried out investigating the effect of zinc deficiency on the metabolism of thyroid hormones in man (21,34) and rats (16,20,24,32). But the results are conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, marginal zinc deficiency has shown to have no influence on the effects of iodine deficiency in rats [25,26]. Other studies [27] demonstrated that thyroid hormone metabolism and function was a complex process and included synthesis of the hormones and prohormones in the thyroid gland, their interconversion by iodothyronine deiodinases in the organs of the body and the binding of T3 to nuclear receptors to control gene expression.…”
Section: Thyroid Hormonesmentioning
confidence: 98%